Rancangan Sistem Penginputan Judul Online KKP, TA/SKRIPSI Berbasis Laravel Pada Universitas Raharja - Cholisoh, Novi; Junaidi, Junaidi; Sari, Irfa Safitri (Technomedia Journal, 2021)
Current technological developments have an effect on the use of software which is always growing rapidly. Currently companies, agencies and others are required to work faster, more precise and accurate and of good quality in the process of managing data and presenting information. Raharja University is one of the tertiary institutions that always improves its quality, especially in the academic field in order to produce excellent students. In carrying out the input of KKP titles, TA / Thesis still use office-based applications, namely using Microsoft Excel, causing sub-optimal performance results due to the length of time required to input and the existence of errors in inputting data. Then a laravel-based online title input application system was built. In research design, a method is needed in order to see the development of the design, the method used in this research is the waterfall model SDLC (System Development Life Cycle) method which is expected to be able to easily determine the achievement of a system, where a title input system has been designed. using PHP (Hypertext Preprocessor) as programming language. In designing the system using the Unified Modeling Language (UML) as a modeling tool consisting of Use Case Diagrams, Activity Diagrams, and Sequence Diagrams. The results of the laravel-based KKP title input system, TA / Thesis are expected to provide solutions to the problems faced. Key words: waterfall, laravel, system, title input